Sex differences in relationship between body composition and digit length ratio (2D:4D) in students of military courses - Kociuba, Marek; Ignasiak, Zofia; Sebastjan, Anna; Kochan, Katarzyna; Cichy, Ireneusz; Dudkowski, Andrzej; Ściślak, Marcin; Kozieł, Sławomir (Anthropological Review, 2018)
It is believed that the second to fourth finger length ratio is an indirect indicator of fetal testosterone levels. It is pointed out that there is a relationship between the 2nd to 4th finger length ratio and the body structure in women and men. Studies on the relationship between body composition and 2D:4D finger length among military students have not been carried out so far. The work aims to determine the dependence of body composition and the quotient of the 2nd and 4th fingers length of military students. The research material has been gathered as a result of examinations of women and men studying military subjects. The study involved 55 women and 65 men. The tests included anthropometric measurements (body height, body weight, length of the second and the fourth fingers) and body composition measurements. As a result of the tests, no dimorphic differentiations in the digit length ratio (2D:4D) was indicated. The BMI, muscle mass, lean body mass and water in the body demonstrated higher values in men than in women. However, the fat content in men was low. It was found that the relationship exists between muscle mass, lean mass and total water content in the body and the 2D:4D finger length ratio in the left hand in women. A higher level of fetal testosterone, characterized by lower values of the 2nd to 4th finger length ratio, may be associated with a higher content of muscle mass, lean body mass and water in the body of adult women leading a similar lifestyle.